Memory quality and misinformation for peripheral and central objects - Wright, Daniel B. (Legal and criminological psychology, 1998)
Purpose. The quality of memories after the presentation of misinformation was explored. Three different types of stimuli were used: a peripheral object, a characteristic of a (different) peripheral object and a central detail. These were chosen in order to achieve different levels of the misinformation effect. Methods. One hundred and eight university students were shown a computer displayed picture sequence of a shoplifting incident. They were then misled about certain aspects. Memory was assessed by forced-choice recognition, ‘remember’/‘know’ judgments and reaction times. Results. Participants often reported ‘remembering’ misinformation for the peripheral object and the characteristic. ‘Remember’ responses were also associated with the fastest reaction times. Conclusions. Misinformation can make people remember errant information. Implications for eyewitness testimony are discussed.